MICROSTRUCTURE AND MECHANICAL PROPERTIES OF DIRECT METAL LASER SINTERED TI-6AL-4V - Becker, Thorsten Hermann; Beck, Mathias; Scheffer, Cornie (The South African Journal of Industrial Engineering, 2015)
Direct metal laser sintering (DMLS) is a selective laser melting (SLM) manufacturing process that can produce near net shape parts from metallic powders. A range of materials are suitable for SLM; they include various metals such as titanium, steel, aluminium, and cobalt-chrome alloys. This paper forms part of a research drive that aims to evaluate the material performance of the SLM-manufactured metals. It presents DMLS-produced Ti-6Al-4V, a titanium alloy often used in biomedical and aerospace applications. This paper also studies the effect of several heat treatments on the microstructure and mechanical properties of Ti-6Al-4V processed by SLM. It reports the achievable mechanical properties of the alloy, including quasi-static, crack growth behaviour, density and porosity distribution, and post-processing using various heat-treatment conditions.